FROM THE TEACHERS' ROOM TO THE DECISION ROOM: THE DYNAMICS OF SCHOOL-BASED MANAGEMENT AT MTSN 3 SIAK - Abdullah; Betri Murni; Indah Efriani Zahara; Nur Kharisma; Anelsa Kintan Famela; Hendri Marhadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
School-Based Management (SBM) is an educational management approach that gives schools greater authority to manage resources, curriculum, and policies to improve the quality of learning in a contextual and participatory manner. The dynamics that occur in schools show an imbalance between formal structures and participatory practices. The purpose of this study is to see how the dynamics of decisions taken in school-based management. The methodology in this study uses a qualitative approach with a case study method at MTsN 3 Siak, which aims to understand in depth the dynamics of decision-making in meeting forums at MTsN 3 Siak as part of the implementation of School-Based Management (SBM). The results of the study found that decisions taken in school-based management at MTsN 3 Siak go through several stages, namely 1) Curriculum-related meetings, 2) School activity meetings 3) Performance evaluation meetings, 4) Daily coordination meetings, 5) Committee/parent meetings, and 6) School innovation team meetings. The conclusion in this study, good decisions in the dynamics of SBM go through several stages involving teachers, staff, students, and parents.